SOME OBSERVATIONS ON THE DISTRIBUTION, MATURITY STAGES AND LENGTH-WEIGHT RELATIONSHIP OF THE ANCHOVY THRYSSA MYSTAX IN THE NORTHERN ARABIAN SEA - Hoda, S M Shamsul (Indian Journal of Fisheries, 2011)
Thryssa mystax (Bloch & Schneider) is abundant along the Karachi andMekran coasts of Pakistan, primarily at depths shallower than 75 m. Maturitystages are described and illustrated. Length-frequency polygons show that thisfish may attain a total length of 140 mm in 1 year. Separate equations of lengthweightrelationships for males and females are presented; their regression coefficientsfrom the Indian coast (Calicut) and from Pakistan coast show differences,suggestive of two separate populations